Proyecto para la reestructuración administrativa de dipaso s. a. distribuidor e importador mayorista y minorista de productos de cuidado personal, cosmética y bazar - Idrovo Romero, Deysi Trinidad (2010)
The following thesis is to find the most viable methodology using various techniques of effective processes to match the everyday processes of each area that has been maintained for years, thus meeting the objectives also are looking to actual customer perception on the processes and services provided DIPASO, in addition to finding those processes that need to restructure their approach for further implementation in the medium and long term The variables used in the CAPM model, the same that aims at finding a rate that represents the minimum return required by investors, it will take into account the risk of the project when the investment is incurred. These are: USA Risk Free Rate (Rf USA), Ecuador's Country Risk, Sector Beta (B) Market Rate of Return (Rm). The CAPM is applied to perfect capital markets, as is the case of United States of America, however in order to reflect the risk in Ecuador, he incorporated the risk of it that is the country risk.